Improved Analytical Approach of Vibration Behavior Destined to Ball Bearings in the Case of Angular Contact - Khalid, El Had; Abdelilah, Hachim; Asmâa, Chouairi; Mohamed, EL Ghorba (Review of Energy Technologies and Policy Research, 2014)
In recent years many developments have been made in the area of the vibration behavior of the supported by bearings or journal bearings rotating shafts. The results, if they are generally acceptable for common-use in terms of operating conditions, are far from meeting the aircraft industry, where the machining at high speeds is an undeniable need. This research therefore is aimed to provide an analytical simulation based on theoretical developments of the vibration response of a ball bearing. The generation of vibration by a point in a rolling element bearing is modeled as a function of the rotation of the bearing, the distribution of the load in the bearing, the transfer function between the bearing, transducer and elasticity of the bearing structure. The essence of this work is to present an analytical model of a specific type single of row effect balls (SKF 6004). This study is a first step dedicated to define the geometric characteristics, and in second time to determine the equations governing the distribution of responsibilities within the ball bearing.